Оптимальні дози хіральних мутагенів в індукуванні видимих мутацій на озимій м'якій пшениці - Катеринчук, О.М.; Чугункова, Т.В. (Фактори експериментальної еволюції організмів, 2013)
Aim. In order to expand the class of mutagens that would allow to obtain new mutant forms of crops, we investigated the optimal dose of chiral nitrosoalkylureas on winter wheat for the first time. Methods. We used standard methods of processing seed mutagens, field and laboratory methods for the analysis of plants in the generation of M1–M3, methods of statistical analysis. Results. The greatest number of mutations in both varieties was induced by the action of S (+) stereoisomer at a concentration of 0,05 %. The frequency of visible mutations in variety Federer ranged from 3,2 % to 9 %, in a variety of Kyrene – from 5 % to 12,6 %. Conclusions. As a result, the effect of chiral stereoisomers on winter wheat was studied. Found that stereoisomers R(-) and S(+) nitroso-sec-butyl-methylureas cause significant mutant changes in the varieties of wheat. The optimal and semi-lethal doses of chiral stereoisomers S(+)NMsBU and R(-)NMsBU for winter wheat seeds were first determined.